An Introduction to Infinite-Dimensional Linear Systems Theory. - Curtain, Ruth F.; Zwart, Hans. (New York, NY : Springer, 1995)
This book introduces infinite dimensional linear systems, treating both state-space and frequency-domain aspects in an integrated fashion that is accessible to graduate engineers and mathematicians with a minimal background in functional analysis.
Texts in Applied Mathematics -- An Introduction to Infinite-Dimensional Linear Systems Theory -- Copyright -- Series Preface -- Preface -- Contents -- List of Figures -- 1 Introduction -- 2 Semigroup Theory -- 3 The Cauchy Problem -- 4 Inputs and Outputs -- 5 Stability, Stabilizability, and Detectability -- 6 Linear Quadratic Optimal Control -- 7 Frequency-Domain Descriptions -- 8 Hankel Operators and the Nehari Problem -- 9 Robust Finite-Dimensional Controller Synthesis -- Appendix A Mathematical Background -- References -- Notation -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: System analysis; Electronic books